2017
DOI: 10.1111/1750-3841.13990
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Effect ofOpuntia ficus‐indicaL. Juice and Seeds Aqueous Extract on Gastric Emptying and Small‐Bowel Motility in Rat

Abstract: This study was conducted to compare the effects of juice and seeds on gastric emptying, small-bowel motility and intestinal ion transport. Separate groups of rats were randomized to receive NaCl, increasing doses of juice (5, 10, and 20 mL/kg, b.w.) or seeds aqueous extract (100, 200, and 400 mg/kg, b.w.). Simultaneously, two other groups were received, the reference drugs; clonidine (1 mg/kg) and yohimbine (2 mg/kg). The charcoal meal was used as a suspension for gastrointestinal motility test. The purgative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Phenol red collected immediately from stomach organs aer test meal administration was used as the standard (0% of GE). 20 GE (%) was calculated according to the following formula:…”
Section: Animalsmentioning
confidence: 99%
“…Phenol red collected immediately from stomach organs aer test meal administration was used as the standard (0% of GE). 20 GE (%) was calculated according to the following formula:…”
Section: Animalsmentioning
confidence: 99%
“…Opuntia ficus indica (L.) fruit (cactus pear) is popular fruit throughout the Mediterranean area and contains minerals, vitamins, fatty acids, sugar, polyphenols and flavonoids. Many studies showed that cactus pear can reduce oxidative stress and may prevent cancer, inflammation and ulcers [1]. The chemical analysis of cactus pear pulp, skin and seeds were studied.…”
Section: Introductionmentioning
confidence: 99%
“…Gastric emptying and small intestinal transit were measured by intragastric administration of the phenol redmethylcellulose (PR-HPMC) method as previously reported [13]. PR-HPMC food was prepared by dissolving 50 mg of phenolic red (Sangon Biotech, Shanghai, China) in 100 mL of 1.5% hydroxypropyl methyl cellulose water solution (Sangon Biotech).…”
Section: Digestive Function Measurementmentioning
confidence: 99%